O ensino de língua inglesa pautado por projetos: um aporte para a implementação da base nacional comum curricular - Lopes, Fernanda (2022)
Other pedagogical work planned by Novo Ensino Médio (BRASIL, 2017) aims at the comprehensive development of the student so that their knowledge is mobilized in the understanding of interdisciplinary issues, to relate them to everyday problems. One of two possible ways to develop this type of work is two work projects from an educational perspective (HERNANDEZ, 1998), which does not imply that the purpose of work and curricular organization includes only “projects”, either, this process is not about implementation of a form or fixed idea, but admits modifications and dialogue with the context. In this historical moment of curricular reforms, in which one of the suggested perspectives for work in schools and work by projects, it is important to have two own professors-researchers with theoretical problems on the subject and, therefore, we justify the choice of the subject of our research. , which seeks to contribute with a gap pointed out by Lucas (2016) that the characteristics of two didactic materials that are few for teachers present, in general, a strong intuitive character and little theoretical base. My research objectives, therefore, analyze how the perspective of Work Projects is characterized in a didactic book and problematize how it can be implemented in a specific context of teaching, taking into account the objectives of English Language teaching foreseen by the Teaching curriculum Middle of the State of São Paulo. The academic relevance of our research consists of a theoretical and methodological contribution from the perspective of a teacher-researcher of basic education and will be able to offer well-founded reflections on aspects of planning, implementation and assessment of teaching.